Brief Report: No Difference in Urine Tenofovir Levels in Patients Living With HIV on Unboosted Versus Dose-Adjusted Boosted Tenofovir Alafenamide. (1st September 2021) - Johnson, Kelly A.; Okochi, Hideaki; Glidden, David V.; Gandhi, Monica; Spinelli, Matthew
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Tenofovir alafenamide (TAF) is increasingly used in HIV treatment, with or without agents that require pharmacologic boosters such as ritonavir/cobicistat. Boosters increase TAF levels, so the TAF dose is lowered in single-pill combinations. We hypothesized that individuals on dose-adjusted boosted TAF would have similar urine tenofovir (TFV) concentrations to those on unboosted TAF. Setting/Methods: We collected urine samples from patients with HIV on TAF, with evidence of virologic suppression and high self-reported adherence at 2 San Francisco clinics from June 2019 to January 2020. We measured urine TFV levels by liquid chromatography/tandem mass spectrometry and used linear regression to compare natural log-transformed urine TFV levels for patients on boosted versus unboosted TAF. Results: Our analysis included 30 patients on unboosted TAF (25 mg daily TAF) and 15 on boosted TAF (12 on 10 mg daily TAF and 3 on 25 mg daily TAF). Patients on unboosted vs. boosted TAF had similar baseline age, weight, sex, and creatinine. In unadjusted univariate linear regression, there were no significant differences in urine TFV levels based on presence/absence of boosting after TAF dose reduction to 10 mg (geometric mean ratio 1.07; 95% confidence interval: 0.53 to 2.16). This finding was unchanged in adjusted analysis. Conclusions: No significant differences in urine TFV levels were seen for patients on unboosted vs. boosted dose-reduced TAF. These results have important implications for our forthcoming point-of-care urine immunoassay for TAF, implying that separate adherence cutoffs will not be necessary for patients on boosters and dose-reduced TAF. A single POC TAF immunoassay will, thus, support monitoring on most TAF-based antiretroviral therapy.